Creating Imaginative Pauses with Sin: The Queer Theological Aesthetics of Oscar Wilde and Paul Cadmus - Fleeson, Nathan E. (Religion and the arts, 2024)
Oscar Wilde and Paul Cadmus both utilize their art to renegotiate how we imagine our relationship to sin within Catholicism. This article draws attention to resonances between their approaches by presenting a Wildean queer theological aesthetic as a framework to interpret Cadmus’s art. A Wildean framework utilizes the excesses of both Catholicism and queerness as a foil for each other to create pauses for the imagination in a culture and religious tradition that risks falling into mechanization. In the space of that excess, we are allowed to escape the trap of existence to live as Individuals, claiming sin as an excess that offers an imaginative pause out of mere existence. Applied to Cadmus, a Wildean framework focuses on how Cadmus’s works also engages queer and Catholic excess to renegotiate Catholic guilt around the body and instead see the body and its sin as a site to know the Self.